STANDARDIZATION OF THE NEW STUDENT ADMISSION PROCESS AT AL-AZHAR 29 BSB ISLAMIC KINDERGARTEN AND PRESCHOOL IN SEMARANG - Avicena Wibiandaru Putri; Muslam (SOSIOEDUKASI, 2026)
This study aims to analyze the implementation of school activity programs in the process of placing new students at KB-TK Islam Al-Azhar 29 BSB Semarang. School readiness assessments are used as the main basis for class grouping and learning strategy planning throughout the school year. This study was conducted because there is still a gap in research on how the concept of school readiness is consistently applied in institutions with dense and development-oriented learning programs. The research used a qualitative method with a case study approach. Data were obtained through in-depth interviews, classroom observations, and assessment document reviews, then analyzed using Miles and Huberman's interactive analysis model through a process of reduction, data presentation, and conclusion drawing. The results of the study show that school readiness assessments play an important role in forming a balanced class composition, supporting differentiated learning strategies, and creating a more stable and inclusive classroom dynamic. The information obtained from mapping children's readiness helps teachers design early interventions and learning routines that are tailored to the developmental needs of each student. In addition, readiness assessments strengthen communication between schools and parents and increase family involvement in the educational process. Overall, the school readiness assessment process not only serves as an administrative procedure but also provides a foundation for more responsive and sustainable learning planning and evaluation.